A quantitative analysis of cloud users' satisfaction and data security in cloud models - Zardari, M.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
The advancement in cloud infrastructure and services is speeding up the rate for organizations to sell their services on a user demand basis. The migration of enterprises to cloud has the same trend as grid and utility computing. However, the cloud infrastructure provides more robust virtualized services despite some security issues such as virtualization vulnerability. Therefore all public clouds are incorporating virtualization technology in their services. There are many cloud service providers available in the market. The new users may suffer from ambiguity as to which cloud will best fit their business needs. We conducted a quantitative survey with the aim to help new users in selecting the best cloud to fit their needs especially for the required services and security. This survey is based on cloud user Small and Medium Enterprises (SMEs) feedback on their existing hired clouds. The users disclosed the pros and cons of their clouds. Aim of this study is to provide information about market oriented cloud to new users which are willing to get cloud services for their SMEs. Â© 2014 The Science and Information (SAI) Organization.